Update on Retinoblastoma Therapies - Cristina A. Martínez Arce; Victor M. Villegas; Maura Di Nicola; Basil K. Williams; Timothy G. Murray (Medicina)
Retinoblastoma is a success story in pediatric oncology, evolving from life-saving interventions to approaches that preserve eyes and vision while minimizing complications. Initially managed with enucleation and radiotherapy, treatment now emphasizes eye preservation through chemotherapy as the cornerstone therapy. Various chemotherapy delivery methods—including intravenous (IVC), intraarterial (IAC), intravitreal, intracameral, and periocular—offer flexibility in treatment. Studies show nearly 100% eye salvage rates for groups A–C. For advanced cases (groups D and E), IAC has achieved outcomes that were not possible before. Intravitreal injections, when performed safely, may help avoid enucleation and radiotherapy in advanced cases, preserving vision, even in complex scenarios, with vitreous seeding. Each strategy may be tailored to tumor and patient characteristics that may help optimize outcomes. Recent innovations like liquid biopsy, prenatal diagnosis, prognostic biomarkers, and new surgical methods, such as tylectomy and chemoplaque, are paving the way for more personalized care. While advanced extraocular or metastatic retinoblastoma remains challenging, these advancements underscore a shift towards better outcomes and individualized management. The future holds promise for refining treatment strategies to maximize eye and vision preservation while ensuring patient survival.